The effect of innovation on sustainable competitive advantage through local wisdom in Padang restaurants in Pekanbaru - Annisa Mardatiilah; Rosmayani Rosmayani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Business competition due to a dynamic business environment that makes Padang restaurant businesses must have the ability to have a sustainable competitive advantage. This study aims to analyze the effect of innovation on sustainable competitive advantage through local wisdom as a mediating variable. A quantitative explanatory approach was used in this study with 100 respondents. It uses the accidental sampling technique of the Padang restaurant business in Pekanbaru. The analytical tool used is PLS, with research showing that innovation affects competitive advantage through local wisdom as a mediating variable. Local wisdom as a mediating variable shows the novelty of this research as a form of cultural integration to achieve sustainable competitive advantage. The unique value contained in the product is a symbol of a strong identity so that it can appear different from competitors. The value of the authenticity and uniqueness of Padang food as a culinary and cultural heritage passed down from generation to generation is different from competitors. So, every innovation made by Padang restaurants in Pekanbaru based on the values of local wisdom will increase sustainable competitive advantage.